Komunikasi Lintas Budaya dalam Implementasi Program Triple Win: Studi Kasus Kerja Sama GIZ, BP2MI, dan Bundesagentur für Arbeit dalam Rekrutmen Perawat Indonesia ke Jerman - Fajar Dwiasputra, Javan Agthian (Jurnal Pendidikan Indonesia, 2025)
Globalization and the global healthcare workforce crisis have driven increased mobility of nurses across borders, one example being the Triple Win Program, which involves collaboration between the Indonesian Migrant Workers Protection Agency (BP2MI), the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ), and the German Bundesagentur für Arbeit (BA). This program is designed to address the need for nursing staff in Germany while simultaneously opening up job opportunities for Indonesian nurses. However, the program's implementation faces complex cross-cultural communication challenges due to differences in values, work systems, and communication styles between Indonesia (high-context, collectivistic, hierarchical) and Germany (low-context, individualistic, egalitarian). This study aims to analyze cross-cultural communication practices among stakeholders in the Triple Win Program, identify communication barriers, and explore adaptation strategies used. Using an interpretive-constructivist paradigm and a qualitative case study approach, data were collected through in-depth interviews, document analysis, and observations of departure training. The research results show five main findings: (1) tensions due to differences in communication styles and cultural values; (2) administrative barriers and misconceptions of terminology; (3) cultural mediation strategies through intercultural training and alumni mentoring; (4) institutional imbalances that place the German side more dominant; and (5) the role of Cultural Intelligence (CQ) as a key to successful adaptation. This research concludes that cross-cultural communication functions not only as a transfer of information, but also as a process of negotiating meaning, power, and identity in international cooperation. Practical implications include the need for intercultural training for all stakeholders, the development of collaborative modules, and strengthening the role of alumni as intercultural agents to increase program sustainability.